The resistance of the intracanal retention thickness with flowable short fiber reinforced composite (SFRC) materials towards fracture toughness - Tania, Isabella Audy; Widyastuti, Wiena (Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Dental hard tissue problems were relatively high in Indonesia. If these problems were ignored, they would cause pulpal necrosis. The main treatment for this case was Root Canal Treatment (RCT). The selection of post-RCT treatment and suitable materials was important. One of the examples was short fiber reinforced composite (SFRC) which can be an option for intracanal retention treatment. This study aims to analyze the resistance of the intracanal retention thickness with flowable fiber reinforced composite materials toward fracture toughness. Methods: This research was using a correlative laboratory experimental method with a post-test group-only design. This study's samples were SFRC material inserted in 27 extracted mandibular first premolars with a length of 21 mm ± 2 mm and root canal walls width of 2 mm. All samples were given intracanal retention at a depth of 2 mm below the orifice and divided into 3 groups: intracanal retention with thickness of (A) 6 mm, (B) 5 mm, and (C) 4 mm. RCT was performed using the crown-down technique. The bonding agent was applied, and then light cured for 20 seconds. SFRC was applied according to the sample group and light cured for 20 seconds per 2 mm, followed by filling with composite resin. The sample was implanted in the dental stone 2 mm below the CEJ. The fracture toughness test was performed using UTM on the occlusal surface with a 0o tilt and crosshead of 1 mm/min. Results: The fracture toughness results of group A, B, and C are 735.44, 756.78, and 829 respectively. Statistical tests with one-way ANOVA showed no significant difference with p value = 0.412 (p < 0.05). Conclusion: There is no difference in resistance of the intracanal retention thickness with flowable fiber reinforced composite materials towards fracture toughness.Keywords: post-RCT treatments, intracanal retentions, SFRC, fracture toughness